The dynamics of social cohesion in response to simulated intergroup conflict in banded mongooses - Preston, EFR; Thompson, FJ; Kyabulima, S; Croft, DP; Cant, MA (Wiley, 2021)
Intergroup conflict is widespread in nature and is proposed to have strong impacts on the evolution of social behavior. The conflict–cohesion hypothesis predicts that exposure to intergroup conflict should lead to increased social cohesion to improve group success or resilience in future conflicts. There is evidence to support this prediction from studies of affiliative responses to outgroup threats in some animal societies. However, most of these studies have focused on behavioral changes over short time periods (minutes and hours after exposure to an outgroup), and hence very little is known about the dynamics and durability of responses to intergroup conflict over the longer term. We investigated this question by simulating intergroup encounters in wild banded mongooses (Mungos mungo) and measuring social behavior before, during, and after these encounters over a 5-day period. We also ran control trials with non-threatening stimuli. Banded mongooses reacted immediately to intrusion stimuli by vocalizing, grouping together, and advancing on the stimulus. In the first 5 min after simulated intrusions, we saw an elevation in grooming levels, but in the hour after exposure grooming rates declined sharply, contrary to our expectation. In the two subsequent days, grooming rates remained at this depressed rate. In control trials, the initial increase in grooming was not seen, but grooming declined compared to the longer-term time periods. Grooming changed across time, but not in the same pattern as during intrusions, suggesting that intrusions had an impact above and beyond that of the experimental setup. The dynamics of grooming responses were short lived and more complex than we initially expected. We suggest this unexpected result may be linked to the frequency of aggressive intergroup encounters in this system. As control and experimental trials were run at different times of year, future work would be needed to confirm that these relative patterns are replicable. Our results indicate short-lived impacts of outgroup threat on measures of social cohesion in this species, but cannot confirm longer-term changes.